Promoted VOC oxidation over homogeneous porous CoxNiAlO composite oxides derived from hydrotalcites: effect of preparation method and doping. Issue 62 (13th June 2016) - Li, Shuangde; Mo, Shengpeng; Li, Jiaqi; Liu, Haidi; Chen, Yunfa
Abstract : Co x NiAlO powdered and film catalysts derived from layered double hydroxide precursors are prepared with excellent catalytic activity, reproducibility, reversibility, and stability to water vapor in benzene oxidation. Abstract : Homogeneous porous and curve plated Co x NiAlO composite metal oxide catalysts are obtained from the thermal decomposition of Co x NiAl-layered double hydroxide (LDH) precursors, which are prepared by urea co-precipitation with surfactant, followed by a hydrothermal treatment. The as-prepared samples were characterized by XRD, BET, SEM, TEM, H2 -TPR and XPS. The Co3 AlO sample shows 90% benzene conversion ( T 90 ) at 236 °C at a high space velocity (SV = 60 000 mL g −1 h −1 ), and possesses much higher activity than Co3 AlO prepared with NaOH co-precipitation without surfactant, with T 90 = 288 °C. This is mainly correlated with the narrower pore size (2.9 vs. 17.2 nm) and lower temperature reducibility (319 vs. 360 °C). The Co2 NiAlO sample exhibits enhanced activity at T 90 = 227 °C with the low activation energy of 39.0 kJ mol −1, and its lower temperature reducibility is ascribed to the larger amount of surface accessible Co 3+ . The Co2 NiAlO sample owns good reproducibility and superior reversibility and long stability with prolonged time on benzene stream in the presence of 3.5% water vapor. Moreover, a monolithic Co2 NiAlO film catalyst is fabricated by the thermal decomposition of an LDH film precursor through an in situ growth methodology, with a high reaction rate of 1.21 mmol g −1 h −1 under T 90 = 275 °C.